Penggunaan Metode Optimasi Particle Swarm Optimization (PSO) Untuk Menentukan Nilai Fasa Optik Optimum Pada Optical Ring Resonators - Anggita Permatasari; Daffi Insan Alif; Herminarto Nugroho (JURNAL TEKNOLOGIA, 2020)
In communication between airplanes and satellite, phased array antennas were needed to receive signals from a specific angle. To satisfy that condition, a controller called Optical Beamforming Network (OBFN) is needed. Process of tuning the OBFN is done by choosing the most suitable parameter as the delay element. Optical Ring Resonators can be used as the delay element. Delay element serves to make the input signal of each PAAs have a same time. This paper will discuss about determination of optical phace optimum value using Particle Swarm Optimization (PSO) method, which has advantages such as fast computing time.